The Effect of Applying Edible Whey Coating with the Addition of VCO (Virgin Coconut Oil) on Mozzarella Cheese - Rahmadani, Lisa; Setiani, Shelina; Melia, Sri; Juliyarsi, Indri (Jurnal Ilmu dan Teknologi Hasil Ternak, 2025)
This study aims to determine the effect of adding Virgin Coconut Oil (VCO) on fat content, protein content, and organoleptic properties. This study used 500 mL of whey obtained from Lassy Dairy Farm in Agam, West Sumatra and VCO produced by UPH KWT BENGKE SAKATO Ambuang Kapua in Padang Pariaman, West Sumatra. The method used in this study was a complete randomized design (CRD) experimental method consisting of 5 treatments and 4 replications. The treatments in this study were the addition of VCO concentrations A (0%), B (1%), C (2%), D (3%), and E (4%). The results obtained from the fat content test showed an average of 17.40-21.72%, protein content with an average of 16.23-19.80%, moisture content test 46.58-48.82%, pH 5.22-5.89, weight loss 11.94-8.15%, the hedonic color test with an average value ranging from 3.08 to 4.42, the hedonic texture test ranging from 2.48 to 4.22, the hedonic aroma test ranging from 1.52 to 4.40, and the overall acceptance value averaging between 2.42 and 3.92. The results of this study indicate that VCO concentration has a significant effect (p < 0.05) on fat content, protein content, organoleptic properties, hedonic color test, texture, and aroma. The best results in this study were obtained in treatment E. Based on these findings, it is recommended to use 4% VCO concentration in edible coating formulations to enhance nutritional value and sensory acceptance. Further research can be conducted to evaluate the antimicrobial or antioxidant properties of the 4% VCO edible coating, as well as its effectiveness in extending shelf life on various food products.